All-optical characterisation of the spintronic Heusler compound Co2Mn0.6Fe0.4Si. (8th April 2015) - Sebastian, Thomas; Kawada, Yuki; Obry, Björn; Brächer, Thomas; Pirro, Philipp; Bozhko, Dmytro A; Serga, Alexander A; Naganuma, Hiroshi; Oogane, Mikihiko; Ando, Yasuo; Hillebrands, Burkard
Abstract: This article is devoted to the evaluation of the material parameters of the Heusler compound Co2 Mn0.6 Fe0.4 Si via Brillouin light scattering spectroscopy. Recently, cobalt-based Heusler compounds and, in particular, the compound Co2 Mn0.6 Fe0.4 Si have attracted huge interest in the fields of spintronics and magnon spintronics. Thus, evaluation of the material parameters that govern spin dynamics in the gigahertz regime is essential to develop and understand advanced experimental scenarios as well as potential technical applications. We demonstrate the evaluation of these parameters based on wavevector as well as time-resolved Brillouin light scattering spectroscopy. The focus of our study is the determination of the spin-wave damping in an individual microstructure as wells as of the exchange constant of Co2 Mn0.6 Fe0.4 Si—parameters, that are difficult to estimate with alternative techniques.